2011
DOI: 10.1021/jo2000012
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Synthesis of Functionalized 2H-Chromenes via Intramolecular Alkyne−Carbonyl Metathesis

Abstract: An iron-catalyzed intramolecular alkyne-aldehyde metathesis strategy of the alkynyl ether of salicylaldehyde derivatives has been developed which works under mild reaction conditions to produce the functionalized 2H-chromene derivatives. This protocol is compatible toward a wide range of functional groups, such as methoxy, fluoro, chloro, bromo, and phenyl groups. This method provides an atom-economical and environmentally friendly approach for the synthesis of a series of substituted 2H-chromenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(35 citation statements)
references
References 46 publications
0
34
0
1
Order By: Relevance
“…Unlike the mechanism proposed by Jana et al, 7 this reaction mechanism involves the initial activation of the alkyne by FeCl 3 followed by nucleophilic attack of the carbonyl on the activated alkyne. This leads to the formation of intermediate 1.2.2-B (Scheme 7).…”
Section: Metal-mediated Approachesmentioning
confidence: 89%
See 2 more Smart Citations
“…Unlike the mechanism proposed by Jana et al, 7 this reaction mechanism involves the initial activation of the alkyne by FeCl 3 followed by nucleophilic attack of the carbonyl on the activated alkyne. This leads to the formation of intermediate 1.2.2-B (Scheme 7).…”
Section: Metal-mediated Approachesmentioning
confidence: 89%
“…Ramachary et al reported 56 a new method for the synthesis of highly substituted (Z)-2-(buta-1,3-dienyl)phenols from highly substituted dienes by a combination of ring-closing metathesis (i) and base-induced ring-opening (ii). The corresponding phenol then transformed to the desired 2-methyl-2H-chromenes via a [1,7]-sigmatropic H-shift reaction followed by electrocyclic ring closure (Scheme 96). Two different reaction conditions were employed: heating at 120− 140°C and treatment with silica at room temperature.…”
Section: Acs Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…1317 This method has been utilized for the conversion of O-propargylsalicylaldehydes into 2H-chromenes in the presence of catalytic amounts of iron(III) chloride. A series of such products could be obtained in good to high yields.…”
Section: Carbonylàalkyne Metathesismentioning
confidence: 99%
“…Synthetic 2H-chromene-3-carboxamide derivatives have also been shown to act as COX-2 inhibitors, 7 central muscle relaxants, 8 analgesics and anti-inflammatories, 9 and as dopamine-D3 ligands. 10 2H-Chromene derivatives have also been accessed via ring-closing metathesis methods, 11,12 while Zhang et al 13 have recently reported the synthesis of 2-trifluoromethyl-6-trimethylsilyl-2H-chromene-3-carboxylic acid derivatives as potential COX-2 inhibitors. 2H-Chromene-3-carboxylic acids have also been obtained efficiently via alkaline hydrolysis of 3-cyano-2H-chromenes which, in turn, were afforded by Baylis-Hillman reactions of 2-hydroxybenzaldehydes with acrylonitrile.…”
Section: Introductionmentioning
confidence: 99%